SAT-178 Incidence, Patterns of Clinical Presentation, and Outcomes of Patients with Brain Metastasis Due to Adrenocortical Carcinoma - Amorim, Larissa Costa (J Endocr Soc, 2020)
Background: Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy, with a heterogeneous but, frequently, dismal prognosis; patients with metastatic ACC have a five-year survival that ranges between 0 and 28%. Metastatic ACC may be present at diagnosis or during follow-up as disease recurrences. The most common sites of metastatic lesions include the liver, lungs, lymph nodes and bones. The brain has only rarely been reported as a site of metastasis in this neoplasia and, to the authors’ knowledge, little is known regarding the incidence, patterns of clinical presentation and disease progression, and outcomes. Objective: The aim of this report was to describe the clinical characteristics of adult patients with ACC who developed brain metastasis evaluated at a tertiary oncological center (ICESP) from Brazil. Methods: Retrospective analysis of medical records including evaluation of laboratory and imaging exams and pathologic data (in cases where surgical resection of the metastasis was performed). Results: In the last ten years (2009-2019), fifty-four patients have been treated for ACC at ICESP; all of them with advanced disease (locally advanced disease and metastatic disease). The median age at the time of diagnosis of ACC was 44 (range 24-61 yrs.). No patients presented metastasis at central nervous system (CNS) at the initial diagnosis; however, during follow-up, we identified brain metastasis in six patients (11.1%). The median time between ACC diagnosis and the detection of brain metastasis was 20.8 months (range 5-53 mo.). In all of these six cases, at least three other sites of metastatic involvement were already present when the brain involvement was diagnosed and, therefore, all of them had already been treated with mitotane in association with at least one line of cytotoxic chemotherapy. The number of brain metastasis in each of these six patients varied from one to eight and median size of lesion was 1.7 cm (range 0.5-4.0 cm). Secondary headache and seizure were the main symptoms of presentation and one or two of these symptoms occurred in all but in one patient, in which diagnosis was due to screening with brain MRI. In four patients with stable disease elsewhere, surgical resection of one or two brain metastases was performed. In these cases, SF1-positive immunohistochemistry confirmed the adrenocortical origin of the lesion. The median time between CNS metastasis detection and death was 3.8 months (range 0.4-59.6 mo.), and complications due to brain metastasis were the leading cause of death. Conclusions: In our institute, brain metastasis occurred in 11.1% of advanced ACC, a prevalence that is higher than previously reported in literature. Despite the relative small number of patients included in this study, we highlight the possibility of brain metastasis in patients with ACC, particularly in cases with a prolonged disease course and multiple systemic treatments.